2002
DOI: 10.1177/1359104502007001005
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Impact on Young Children of Maternal HIV Serostatus Disclosure

Abstract: A B S T R A C TA longitudinal analysis of the psychological well-being of 81 young children ages 6-11 living with their HIV symptomatic or AIDS diagnosed mothers was conducted. Specifically, the relationship among mothers' disease severity, maternal disclosure of HIV, and children's psychological well-being was investigated. The children were assessed over three time points (i.e. baseline assessment, 6-month and 1-year follow-up). Two categories of maternal disclosure (disclosed before baseline, no disclosure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 22 publications
3
60
1
Order By: Relevance
“…Consonant with results from several studies of the relationship between illness disclosure and child psychosocial adjustment (Armistead et al, 1997(Armistead et al, , 2001Murphy et al, 2001;Murphy, Marelich et al, 2002), disclosure was not related to teacher, mother, or child reports of child functioning. As suggested by Armistead and colleagues (2001), the presence of potentially positive consequences of disclosure (e.g., lower maternal stress), as well as unsalutary effects (e.g., increased child stress) may balance each other out thereby explaining the null finding.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Consonant with results from several studies of the relationship between illness disclosure and child psychosocial adjustment (Armistead et al, 1997(Armistead et al, , 2001Murphy et al, 2001;Murphy, Marelich et al, 2002), disclosure was not related to teacher, mother, or child reports of child functioning. As suggested by Armistead and colleagues (2001), the presence of potentially positive consequences of disclosure (e.g., lower maternal stress), as well as unsalutary effects (e.g., increased child stress) may balance each other out thereby explaining the null finding.…”
Section: Discussionmentioning
confidence: 49%
“…Various rates of disclosure of parental HIV/AIDS to children have been reported, ranging from 0% (Esposito et al, 1999) to 74% (Armistead et al, 1997(Armistead et al, , 2001Bauman et al, Camacho et al, 2002;Forsyth et al, 1996;Lee & Rotheram-Borus, 2002;Murphy et al, 2001;Murphy, Marelich et al, 2002;Nagler et al, 1995;Niebuhr et al, 1994;Nostlinger et al, 2004;Ostrom et al, 2006;Pilowsky et al, 1999;Rotheram-Borus et al, 1997;Schrimshaw & Siegel, 2002;Shaffer et al, 2001;Sowell et al, 1997;Tompkins et al, 1999;Wiener et al, 1998), and likely depend on such factors as child age, disease progression, quality of the parent-child relationship, and general cultural influences on disclosure-and child-related beliefs. Although parents commonly cite protection from distress as a major reason for withholding illness-related information from children, clinical observation indicates that children typically have some sense that something is wrong anyway (Melvin, 1996).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although recent research has suggested that disclosure of disease status may influence youth mental health, results have been mixed in terms of whether awareness is associated with higher (e.g., Lee & Rotheram-Borus, 2002) or lower (e.g., Murphy, Marelich, & Hoffman, 2002) rates of negative child/adolescent outcomes. For example, using the current sample of participants, Tompkins (in press) found no differences in child functioning between the 61% of the HIV-affected families whose children were aware of their mothers' illness and those who were not informed.…”
Section: Introductionmentioning
confidence: 99%